2017
DOI: 10.1088/1361-6587/aa5952
|View full text |Cite
|
Sign up to set email alerts
|

Phase-space dynamics of runaway electrons in magnetic fields

Abstract: Dynamics of runaway electrons in magnetic fields are governed by the competition of three dominant physics: parallel electric field acceleration, Coulomb collision, and synchrotron radiation. Examination of the energy and pitch-angle flows reveals that the presence of local vortex structure and global circulation is crucial to the saturation of primary runaway electrons. Models for the vortex structure, which has an O-point to X-point connection, and the bump of runaway electron distribution in energy space ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
45
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(49 citation statements)
references
References 26 publications
4
45
0
Order By: Relevance
“…gives parametric scaling laws for the attractor position and width. The momentum scaling law coincides with the prediction of the single particle trajectory analysis[119] and in general agreement with the numerically verified force balance estimates of[69] and[126]. Incidentally, these scaling laws differ from what is predicted by Eq.…”
supporting
confidence: 84%
“…gives parametric scaling laws for the attractor position and width. The momentum scaling law coincides with the prediction of the single particle trajectory analysis[119] and in general agreement with the numerically verified force balance estimates of[69] and[126]. Incidentally, these scaling laws differ from what is predicted by Eq.…”
supporting
confidence: 84%
“…the partial screening effect, which has a direct dependence on the ion charge state distribution, according to Hesslow et al [21,36]. The physical importance is that enhanced pitch angle scattering would limit the energy of the O-point of the runaway vortex, which is responsible for a lower runaway energy but broader pitch distribution [37,38]. The runaway-induced ionization would then modulate the pitch angle scattering rate due to partial screening, impacting both the avalanche threshold and runaway energy distribution, as well as the spatial transport of the runaways [39].…”
Section: Runaway-induced Ion Charge State Effectsmentioning
confidence: 99%
“…Early models taking into account small angle Coulomb collisions [5] and later large angle collisions [6] identified the crucial role of the 'critical electric field' (E C ), which defines the electric field at which collisional drag balances electric field acceleration in the relativistic limit. Later work * paz-soldan@fusion.gat.com identified the potential for synchrotron damping to elevate the effective E C [7,8], and more recently analytic treatments [9] and computational methods [10][11][12][13][14][15][16] were developed to combine the effects of synchrotron damping and pitch-angle scattering off high-Z ions. These works confirmed that synchrotron and pitch-angle scattering can together elevate the effective E C above early model predictions.…”
Section: Introductionmentioning
confidence: 99%